Paul, Romans, and the Christians at Rome - Hultgren, Arland J. (Word & world, 2019)
As with any work, it is important to understand who the key figures are - the writer, the audience, and the context. This article sets out the basic structure of the Letter to the Romans by keying in the three major elements of this work: Paul as the writer, the Christians in Rome as the audience, and the culture and structure of the city of Rome as its context.